Tumor-Infiltrating Lymphocytes in Colorectal Cancer: The Fundamental Indication and Application on Immunotherapy - Bai, Ziyi; Zhou, Yao; Ye, Zifan; Xiong, Jialong; Lan, Hongying; Wang, Feng (Frontiers in Immunology, 2022)
The clinical success of immunotherapy has revolutionized the treatment of cancer patients, bringing renewed attention to tumor-infiltrating lymphocytes (TILs) of various cancer types. Immune checkpoint blockade is effective in patients with mismatched repair defects and high microsatellite instability (dMMR:MSI-H) in metastatic colorectal cancer (CRC). In contrast, patients with proficient mismatch repair and low levels of microsatellite stability or microsatellite instability (pMMR:MSI-L/MSS) typically have low tumor-infiltrating lymphocytes and have shown no response to the immune checkpoint inhibitor. Different TILs environments reflect different responses to immunotherapy, highlighting the complexity of the underlying tumor-immune interaction. In this review, we summarize the subsets-specific nature of TILs in CRC and their association with the prognosis of CRC patients. We also discuss current clinical immunotherapy approaches based on TILs and future directions for expansion, and highlight existing clinical data supporting its use.